Combining biodelignification and hydrothermal pretreatment of oil palm empty fruit bunches (OPEFB) for monomeric sugar production. (September 2021) - Hidayatullah, Ibnu Maulana; Al Husna, Muhammad Daris; Radiyan, Husni; Kresnowati, Made Tri Ari Penia; Suhardi, Sri Harjati; Setiadi, Tjandra; Boopathy, Ramaraj
Abstract: Oil palm empty fruit bunches (OPEFB) is the most abundant agro-industrial waste in Indonesia. It has 22.03–35% hemicellulose content. This paper reports the delignification of OPEFB using white-rot fungi followed by hydrothermal pretreatment to enhance the xylose and glucose production. The study was conducted by comparing the performance of two different species of white-rot fungi ( Marasmius sp. and Phanerochaeta chrysosporium ) in OPEFB mass loss, the ability to degrade lignin and hydrolyze OPEFB that had been treated enzymatically at various cultivation times. Marasmius sp. (26.67%) achieved the best lignin degradation ability during 20 days of cultivation. The best xylose recovery (166 mg/g OPEFB) and glucose recovery (283 g/g OPEFB) occurred at bio-delignification using Marasmius sp. for 30 days, followed by hydrothermal pretreatment for 15 min at a temperature of 160 °C. The combination of these two pretreatments increased monomeric sugar yield over the length of cultivation time. Graphical abstract: Unlabelled Image Highlights: Use of white rot fungi enhanced the sugar yield from hydrothermal pretreated OPEFB. Delignification of OPEFB by white rot fungi was significant. Phanerochaeta chrysosporium degraded lignin-holocellulose better than Marasmius sp. Marasmius sp. showed higher xylose and glucose yields than Phanerochaeta chrysosporium in OPEFB delignification.